Ukraine's crimes against humanity 2022-2023 - Grigoriev, Maxim (Foundation for Study of Democracy, Moscú, 2023)
The book «Ukraine's Crimes Against Humanity (2022-2023)» contains more than 400 testimonies of victims and eyewitnesses of Ukrainian war crimes and terrorist acts against civilians, committed between 2022 and 2023. These testimonies have been collected by various public initiatives and organizations, including the International Public Tribunal on the Crimes of Ukrainian Neo-Nazis and Their Accomplices, the Foundation for the Study of Democracy, and many others